Structural Needs, Substance Use, and Mental Health Among Transgender and Nonbinary Young Adults in the San Francisco Bay Area: Findings from the Phoenix Study. - King, Wesley M.; Gamarel, Kristi E.; Iwamoto, Mariko; Suico, Sabrina; Nemoto, Tooru; Operario, Don (Journal of Urban Health, 2023)
Transgender and nonbinary (trans) young adults report high rates of substance use and adverse mental health outcomes; however, few studies have examined how social, economic, and legal factors may contribute to health inequities in this population. Guided by the structural vulnerability framework, this study sought to explore structural needs and whether these needs were associated with substance use and mental health outcomes among trans young adults. Between 2019 and 2021, 215 trans young adults aged 18–29 from San Francisco Bay Area were recruited into a longitudinal study. Baseline data were used to examine bivariate and multivariable associations between structural needs and substance use and mental health outcomes. There were bivariate differences in the number of structural needs by education, income source, incarceration history, and ethnicity, and the number of unmet structural needs was associated with education and income source. After adjusting for sociodemographics, the number of structural needs was associated with daily marijuana use (AOR 1.29, 95% CI: 1.10–1.49) and suicidal ideation (AOR 1.24, 95% CI: 1.06–1.45), and the number of unmet structural needs was associated with daily marijuana use (AOR 1.30, 95% CI: 1. 10–1.55) and depressive symptoms (β 2.00, 95% CI: 1.00–3.00). Additionally, both numbers of structural needs and unmet structural needs mediated the relationship between income source (traditional employment vs. other income only) and depressive symptoms (TIE β 2.51, 95% CI: 0.99–4.04; β 1.37, 95% CI: 0.23–2.52, respectively). Findings highlight a need for multisector efforts to address structural vulnerabilities among trans young adults.